Green and traditional one-pot synthesis techniques for bioactive quinoline derivatives: A review - Manav C. Parmar; Bonny Y. Patel (Tetrahedron Green Chem)
The review examines one-pot strategies and their mechanistic approaches for synthesizing the quinoline nucleus from 2009 to 2024, with a focus on their therapeutic potential. The paradigm shifts from conventional synthetic protocols to advanced green methodologies has revolutionized the synthesis of quinoline derivatives. Strategies that adhere to sustainable chemistry principles by minimizing waste, solvent consumption, and energy input. Various green catalysts, including p-toluenesulfonic acid (p-TSA), para-sulfonic acid calix[4]arene (CX4SO3H), cerium nitrate, ammonium acetate, potassium carbonate (K2CO3), and catalyst-free techniques, have proven effective in synthesizing quinoline analogs. The use of greener solvents such as ethanol and water further supports the eco-friendly synthesis of these compounds. The review also highlights a broad spectrum of pharmacological activities of quinoline derivatives, including antibacterial, antiviral, antidiabetic, anticancer properties and so on. SAR studies show that adding EDGs (-CH3, –OCH3, –OH) and EWGs (-Cl, –F, –NO2, –CF3) can enhance electronic properties, lipophilicity, and receptor-binding affinities. Moreover, hybridization with heterocyclic scaffolds such as furan, pyrazole, indole, and thiadiazole significantly improves bioactivity, demonstrating the intricate relationship between structural modifications and biological efficacy. By merging sustainable chemistry with targeted pharmacological strategies, quinoline-based compounds emerge as innovative candidates for diverse clinical applications.